Educational Policy in Uzbekistan: Experience and Modernization Processes - Mavlonov Jurabek Yorqulovich; Bo'riyev Ibrohim Salohiddin ogli (Scientific Trends, 2025)
This article analyzes the development, experience and modernization processes of educational policy in Uzbekistan. The article examines the reforms implemented in the field of education after Uzbekistan gained independence, international experience and the introduction of digital technologies. The economic and social impact of changes in the education system, the introduction of new methodologies, innovative approaches and digital educational technologies aimed at improving the quality of the educational process, is shown. The article also provides proposals and recommendations for further improvement of educational policy, with special attention paid to ensuring the global integration of the Uzbek education system, the application of innovations and its development based on modern requirements.
Keywords: Uzbekistan, education policy, reforms, modernization, digital education, international experience, innovative approaches, teaching methodology, education system, economic impact, social impact.